Pengembangan Bahan Ajar Mata Pelajaran Sosiologi Siswa Madrasah Aliyah - Wagimin Wagimin (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2017)
Abstract Penelitian ini bertujuan untuk mengembangkan perangkat materi pembelajaran untuk pengajaran sosiologi guna memotivasi siswa. Penelitian ini menggunakan metode penelitian dan pengembangan guna menformulasi produk dan mengukur efektifitasnya melalui validasi dan pengujian ahli di bidangnya. Ada tiga tipe test yang digunakan yaitu, one to one, small group, dan field test yang menunjukkan bahwa desain materi tersebut efektif. Setelah melalui revisi, desain meteri pembelajaran Sosiologi dianggap bermanfaat dan dapat digunakan dalam proses belajar mengajar Kata Kunci: Perangkat pembelajaran, mata pelajaran Sosiologi, siswa Madrasah Aliyah Abstract [Tittle: The Development of Sosiology Instructional Material for The Students fo Islamic Senior High School] . The research aims at developing a set of instructional material for teaching Sociology in order to motivate the students. The researcher employed a research and developing method to formulate a product and to measure its effectiveness through validation and trial-out by the experts of content-material and material-design. There were three types of trial to test the design; one to one, small group, and field test. Based on the test result, it was found that students in average can achieve 84% of overall score which indicate that the designed material is effective. After being revised several times in each stage, the design of instructional material for Sociology subject is considered as beneficial and able to be used in the teaching learning process